2021
DOI: 10.1088/1742-6596/1977/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of flow structures in twin-rotors wakes in drones by time-resolved PIV

Abstract: An experimental investigation of the noise emissions of a twin-rotor together with the evolution and spatial organization of the flow structures wakes has been carried out by means of aeroacoustics and time-resolved PIV (TR-PIV) measurements. Each rotor is characterized by three bladed propellers with diameter D = 393.7 mm running at four different rotational speeds (2620, 3500, 4360, 5200 RPM). Intricate flow patterns characterized by periodic vortical structures are formed in the wake of the rotors in twin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…This indicates that the rotor wake at V d /V h = 1.08 lies in a flow state referred to as incipient VRS, wherein the flow switches intermittently between the VRS and tubular topologies. This result agrees with those presented in earlier studies (Newman et al 2003;Green et al 2005), which observed the intermittent transition of the rotor wake into a VRS form at the onset of VRS. Figures 6(e, f ) show the representative instantaneous fields of the rotor wakes at V d /V h = 1.30 and 1.52, respectively.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates that the rotor wake at V d /V h = 1.08 lies in a flow state referred to as incipient VRS, wherein the flow switches intermittently between the VRS and tubular topologies. This result agrees with those presented in earlier studies (Newman et al 2003;Green et al 2005), which observed the intermittent transition of the rotor wake into a VRS form at the onset of VRS. Figures 6(e, f ) show the representative instantaneous fields of the rotor wakes at V d /V h = 1.30 and 1.52, respectively.…”
Section: Resultssupporting
confidence: 93%
“…Lee et al (2021) suggested a modelling equation to predict the tip vortex trajectory considering the effect of rotor-rotor interaction during hovering for multi-rotor configurations. Wake characteristics that are complicated by the rotor-rotor interaction significantly affect the aerodynamic performances of multi-rotor systems, including the mean thrust generation (Intaratep et al 2016;Yoon et al 2016;Zhou et al 2017;Lee & Lee 2020;Veismann & Gharib 2020;Lee et al 2021), force fluctuations (Zhou et al 2017;Lee & Lee 2020) and noise (Intaratep et al 2016;Zhou et al 2017;Lee & Lee 2020;Nargi et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For the code validations, the results obtained by each partner were shared among the action group. Three data bases of test data were available from DLR [2][3], CIRA/CUSANO [4] [5] and Polimi [6]. In addition, the first common test campaigns involving PIV measurement were carried out by CIRA/DLR [7], using the DLR small rotor configurations [2] [3].…”
Section: Introductionmentioning
confidence: 99%
“…1 Aerodynamics and aero-acoustics of propellers and rotors have been under investigation for decades. 3,4 Examples of previous aero-acoustic research have focused on a single isolated rotor (without a wing underneath), 1,[5][6][7][8][9] two or multiple tandem rotors (without a wing underneath), [10][11][12][13] and scaled tiltrotor models (with a wing underneath): V-22 14 and XV-15. [15][16][17] The aforementioned aeroacoustic studies on the V-22 (Figure 1 31 (c) Germandrones Songbird, 32 and (d) Wingcopter.…”
Section: Introductionmentioning
confidence: 99%